Design of a chocolate tempering machine with thermosyphon installation – a new concept study - Parametthanuwat Thanya; Bhuwakietkumjohn Nipon; Sichamnan Surachet; Booddacha Khridsadakhon; Wongsa Jittimon (E3S Web of Conferences)
This research presents a case study of applying a thermosyphon for energy conservation in a chocolate temper process. The use of the thermosyphon, made of 304 stainless steel, aimed to achieve a uniform temperature distribution, control temperature and reduce electric consumption. The results show that processing time and electric consumption could be reduced by 10%. The quality of crystallisation and texture of the chocolate tempering exceeded manufacturing standards.